Cryptosporidium infection in school children in Dhanusha district, Nepal - Yadav, Nagendra Prasad; Sah, DK; Manadhar, S; Singh, JK (Janaki Medical College Journal of Medical Science, 2013)
Background and Objectives: Gastro-intestinal water-borne infections are among the most emerging and re-emerging infectious diseases throughout the world. Most water-borne diseases are caused by organism ranging from microscopic viruses of less than 30 nm in diameter to parasites of 10cm in length culminate into diarrhea and cause approximately 5million reported deaths annually. The purpose of the present study was to evaluate the prevalence of intestinal parasites, Cryptosporidium parvum among school children. Material and Methods: The study was carried out between Februry to July 2012. Cases of diarrhea reported in 23 students were linked to water handling practices. A total 500 of child of age less than 15 years old was included in the study. A total five hundred soft, loose or watery stool specimens collected from student of less than fifteen years from different school in Janakpur. The sample was collected randomly from randomly selected five schools. The collected stool samples were screened for the presence of Cryptosporidium oocysts. A modified Ziehl Neelsen with DMSO staining method was used for detecting Cryptosporidium oocysts in the stool samples. Results: The oocysts of Cryptosporidium were identified in 64 (6.8%) of the samples, while 242 samples (13%) showed mixed infections. Children aged between 3 and 10 years were mostly infected by this parasite, while infection was more prevalent in females than in males for all the age groups. Conclusion: The study suggests that Cryptosporidium is one of the important intestinal parasites of children as etiologic agents of diarrhea in immune-compromised population. Janaki Medical College Journal of Medical Sciences (2013) Vol. 1 (2): 40-45 DOI: http://dx.doi.org/10.3126/jmcjms.v1i2.9268